PENGEMBANGAN MODUL PEMBELAJARAN FISIKA TERINTEGRASI KEARIFAN LOKAL TAGANING UNTUK KETERAMPILAN KONSEPTUAL GELOMBANG MEKANIK - Purba, Bulus Tua M.; Marbun, Juliaster; Sinaga, Goldberd Harmuda Duva; Surbakti, Mariana; Sitorus, Parlindungan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
Conceptual skills in physics are an essential foundation for students to understand natural phenomena deeply and analytically, yet conventional teaching often fails to connect abstract theory with real-life contexts. This study aims to develop a physics learning module integrated with the local wisdom of the Toba Batak Taganing on mechanical wave material to enhance students' conceptual skills. The developed module links concepts of waves, resonance, and interference with the acoustic principles of the Taganing musical instrument through a Problem-Based Learning approach. Expert validation results demonstrated a high level of feasibility, with details of 78% (Feasible category) by subject matter experts, 85% (Highly Feasible) by cultural experts, and 97% (Highly Feasible) by language experts. A limited trial with grade XI students showed an improvement in conceptual skills, specifically an abstraction ability of 71% (Good) and systematic thinking of 72% (Good). Teacher and student responses to the module were very positive, with a practicality level of 81%, indicating that the module is not only easy to use but also contextual and engaging. These findings confirm that integrating local wisdom into ethnoscience-based physics learning design is not only effective in strengthening students' conceptual understanding but also plays a strategic role in preserving cultural heritage and fostering learning engagement.